STUDI IN SILICO NANOPARTIKEL PERAK BUNGA TELANG SEBAGAI ANTIBAKTERI - Septian Dwi Mulyana; Nur An Nitta Rizki Fanani; Thiya Rahma Karina; Khoirun Niswatunnisa Niswatunnisa; Nadine Detta Rezza Nevanda; Septiara Dwi Ariyanti (JURNAL PHARMA BHAKTA, 2026)
Background: Antibacterials are compounds with the ability to slow down and inactivate pathogenic bacteria that can cause inflammation and abscess formation. Silver nanoparticles (AgNP) are metal particles measuring 1–100 nm that are known to have high antibacterial potential. In the formation process, a reducing agent is required to facilitate chemical interactions. Butterfly pea flower (Clitoria ternatea) is used as the active ingredient in the synthesis of silver nanoparticles based on green synthesis, where flavonoid compounds act as reducing agents. Objective: To determine the potential of butterfly pea flower quercetin as an antibacterial agent through in silico studies. Methods: The study was conducted in silico with protein 6J90 as the receptor and quercetin as the test ligand, with preparation through geometry optimization and molecular docking validation. Drug-likeness, pharmacokinetic, toxicity, and ligand– receptor interactions were analyzed using Lipinski’s rule of five, PreADMET, Toxtree, AutoDock Tools, and Discovery Studio. Results: The study showed that the test compound met drug-likeness criteria, had a good pharmacokinetic profile, and was not carcinogenic with a safe exposure limit of ≤0.15 µg/day, with a binding affinity value of −5.96 kcal/mol that was more stable than the natural ligand. Conclusion: In silico studies show that quercetin from butterfly pea flower silver nanoparticles has potential as an antibacterial agent, with a binding affinity value of −5.96 kcal/mol to the 6J90 protein, which is more stable than natural ligands.